Induced Pluripotent Stem Cells in Cardiovascular Medicine - Toru Egashira; Shinsuke Yuasa; Keiichi Fukuda (Stem Cells International)
Induced pluripotent stem (iPS) cells are generated by reprogramming human somatic cells through the forced expression of several embryonic stem (ES) cell-specific transcription factors. The potential of iPS cells is having a significant impact on regenerative medicine, with the promise of infinite self-renewal, differentiation into multiple cell types, and no problems concerning ethics or immunological rejection. Human iPS cells are currently generated by transgene introduction principally through viral vectors, which integrate into host genomes, although the associated risk of tumorigenesis is driving research into nonintegration methods. Techniques for pluripotent stem cell differentiation and purification to yield cardiomyocytes are also advancing constantly. Although there remain some unsolved problems, cardiomyocyte transplantation may be a reality in the future. After those problems will be solved, applications of human iPS cells in human cardiovascular regenerative medicine will be envisaged for the future. Furthermore, iPS cell technology has generated new human disease models using disease-specific cells. This paper summarizes the progress of iPS cell technology in cardiovascular research.